Knock damage in spark-ignition engines - Nates, Roy Jonathan (Department of Mechanical Engineering, 2015)
The objectives of this thesis were to identify, explain and quantify the damage caused by knocking combustion in spark-ignition engines. A literature review indicated that, in general, research into knock has focused on the causes and avoidance of knock, rather than on the damage resulting from knock. The few published works concerning the effects of knock were mainly interested in the prevention of one specific form of damage, namely piston erosion. The review highlighted the need to investigate the relationship between knock and the various forms of damage. Using the evidence from knock-damaged engines, the sequence of events leading to failure were reconstructed. The manner in which knock damage manifests itself as surface erosion, piston-ring failure, piston-land cracking, piston blow-by and seizure were examined. From these observations it was deduced that two independent damage paths result from knock. Consequently, the research diverged into two studies, namely: Local pressure-temperature transients in the end-gas zone which cause localised erosion damage; Excessive heat flux associated with knocking combustion which results in global piston and ring problems.